فاعلیة استخدام الشبكة التدریبیة في عدد من المتغیرات البدنیة لدى لاعبي كرة القدم للشباب - هادي احمد خضر (physical education and sport sciences college for women/ Baghdad University, 2018)
In football today is trying all control opponent moves the team and narrowing the space and reduce the time given to them to look forward and think .. and the use of the training network in the training provides us with situations similar to what is in modern football, and lines that define these boxes inside the network represent litigants and when out of the ball, the the player loses possession playing this way develop the players capabilities to play within the positions emphasizes the censorship as well as read the game before getting on the ball, and training in these boxes restricts freedom of play and freedom of movement and mastery of playing in them will be the game easier proportions players good and lies the importance of research in the players trained inside different restricted areas of the pitch, or the so-called (training network) to see the impact of training curriculum proposal using the training network and style interval training on the development of certain physical variables for players young reel youth football in order to improve performance piece level and raise it for the better, is the research problem that the development of physical attributes and to respond to the positions of the changing need special quality in line with the positions of play constantly changing, the impact of the use of the training network style training interval on some physical variables for players young football researcher used the experimental method for suitability and the nature of the research design groups Equalresearch community of players Zakho Sports Club in the province of Dohuk game football for a year (2016) under the (19) years and totaling 53 players were used several means statistically to get the results were analyzed and discussion of results and was the most important conclusions of the latest proposed training curriculum using training network positive impact on physical variables relevant research the most important recommendations Confirmation to use this method in training during periods of public and private numbers